2019
DOI: 10.1017/s1755773919000274
|View full text |Cite
|
Sign up to set email alerts
|

Voters reward hard-working MPs: empirical evidence from the French legislative elections

Abstract: This paper studies the relationship between incumbent MPs’ activities and their electoral fortune. We address this question in the context of the French political system characterized by an executive domination, a candidate-centered electoral system, and an electoral schedule maximizing the impact of the presidential elections. Given the contradictory influence of these three institutional features on the relationship between MPs’ activities and electoral results, the overall link can only be assessed empirica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…It seems that ‘valence’ productivity – engaging in activities that are universally considered ‘good’ – is more important than engaging in either technical, obscure activities or ‘show-horse’/ theatrical ones. This is in line with what was theorised by Ferejohn (1986) and with the empirical findings from the literature on the activity-vote link (François and Navarro, 2019, 2020; Papp and Russo, 2018). Future research should investigate the mechanism behind the association found between different activities and voting behaviour more in detail.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It seems that ‘valence’ productivity – engaging in activities that are universally considered ‘good’ – is more important than engaging in either technical, obscure activities or ‘show-horse’/ theatrical ones. This is in line with what was theorised by Ferejohn (1986) and with the empirical findings from the literature on the activity-vote link (François and Navarro, 2019, 2020; Papp and Russo, 2018). Future research should investigate the mechanism behind the association found between different activities and voting behaviour more in detail.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, it is important to further explore the conditions under which different legislative records can shape voting behaviour (François and Navarro 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By initiating legislation and asking written questions to the government, MPs can, for instance, raise their personal profile and become better known to their voters. There is thus a direct link between what MPs do during their term and their reputation, which may in turn contribute to explain the positive relationship between MPs’ activities and their chances of re‐election (François and Navarro ). On the other hand and as hypothesised, not all activities matter: leadership positions within the assembly, oral questions and the drafting of legislative reports, in particular, do not provide the benefits which could be expected.…”
Section: Discussionmentioning
confidence: 99%